Myocardial nulling pattern in cardiac amyloidosis on time of inversion scout magnetic resonance imaging sequence – A new observation of temporal variability - Mahalingam, Harshavardhan; Chacko, Binita Riya; Irodi, Aparna; Joseph, Elizabeth; Vimala, Leena R; Thomson, Viji Samuel (Indian Journal of Radiology and Imaging, 2018)
Context: The pattern of myocardial nulling in the inversion scout sequence [time of inversion scout (TIS)] of cardiac magnetic resonance imaging (MRI) is an accurate tool to detect cardiac amyloidosis. The pattern of nulling of myocardium and blood at varying times post gadolinium injection and its relationship with left ventricular mass (LVM) in amyloidosis have not been described previously. Aims: The aim is to study the nulling pattern of myocardium and blood at varying times in TIS and assess its relationship with LVM and late gadolinium enhancement (LGE) in amyloidosis. Materials and Methods: This was a retrospective study of 109 patients with clinical suspicion of cardiac amyloidosis who underwent MRI. Of these, 30 had MRI features of amyloidosis. The nulling pattern was assessed at 5 (TIS5min) and 10 (TIS10min) minutes (min) post contrast injection. Nulling pattern was also assessed at 3min (TIS3min) in four patients and 7min (TIS7min) in five patients. Myocardial mass index was calculated. Mann-Whitney U test was done to assess statistical difference in the myocardial mass index between patients with and without reversed nulling pattern (RNP) at TIS5min. Results: RNP was observed in 58% at TIS5minand 89.6% at TIS10min. Myocardial mass index was significantly higher in patients with RNP at TIS5min[mean = 94.87 g/m2; standard deviation (SD) =17.63) when compared with patients with normal pattern (mean = 77.61 g/m2; SD = 17.21) (U = 18; P = 0.0351). Conclusion: In cardiac amyloidosis, TIS sequence shows temporal variability in nulling pattern. Earlier onset of reverse nulling pattern shows a trend toward more LVM and possibly more severe amyloid load.
Keywords: Amyloidosis; cardiac; magnetic resonance imaging; TI scout